2013
DOI: 10.1364/ol.38.001395
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation of nonuniformly correlated beams in atmospheric turbulence

Abstract: We investigated the scintillation properties of nonuniformly correlated (NUC) beams in atmospheric turbulence and have shown that NUC beams can not only have lower scintillation but also higher intensity than Gaussian-Schell model beams and even higher intensity than coherent Gaussian beams over certain propagation distances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(28 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Since the sufficient condition for devising a genuine correlation function of a scalar or electromagnetic partially coherent beam was established by Gori and collaborators [3,4], a wide variety of partially coherent sources and beams became known, such as beams with locally varying spatial coherence [5], a nonuniformly correlated (NUC) beam [6][7][8][9], multi-Gaussian Schellmodel (MGSM) beam [10][11][12][13], cosine-Gaussian Schellmodel (CGSM) beam [14,15], Bessel-Gaussian (BGSM) and Laguerre-Gaussian Schell-model (LGSM) beam [16,17], and a special correlated partially coherent vector beam [18]. All these beams exhibit interesting features.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the sufficient condition for devising a genuine correlation function of a scalar or electromagnetic partially coherent beam was established by Gori and collaborators [3,4], a wide variety of partially coherent sources and beams became known, such as beams with locally varying spatial coherence [5], a nonuniformly correlated (NUC) beam [6][7][8][9], multi-Gaussian Schellmodel (MGSM) beam [10][11][12][13], cosine-Gaussian Schellmodel (CGSM) beam [14,15], Bessel-Gaussian (BGSM) and Laguerre-Gaussian Schell-model (LGSM) beam [16,17], and a special correlated partially coherent vector beam [18]. All these beams exhibit interesting features.…”
mentioning
confidence: 99%
“…All these beams exhibit interesting features. The NUC beam displays a self-focusing effect and a lateral shift of the intensity maximum on propagation [6][7][8][9]. The MGSM beam displays a far-field flat-topped beam profile [10][11][12][13].…”
mentioning
confidence: 99%
“…The evolution properties of the scintillation of an NCPC beam in atmospheric turbulence was illustrated in Ref. [20], and it was found that an NCPC beam can not only have lower scintillation but also higher intensity than a conventional Gaussian-Schell-model (GSM) beam, and it will be useful for long-distance free-space optical communications. Recently, the scalar NCPC beam was extended to the electromagnetic case [21] and the statistical properties of such beam in turbulent atmosphere were also investigated [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Gu and Gbur investigated the NUC beam in atmosphere and found it to have superior scintillation characteristics [35]. The scintillations of multi-Gaussian Schell-model (MGSM) beams were investigated by Yuan et al theoretically [36] and Korotkova et al experimentally [37], and also found to have reduced scintillation.…”
Section: Introductionmentioning
confidence: 99%